Improvement of Solid-Gas Interaction in Fluidized Bed Systems via Secondary Air- Injection - Mohideen Batcha Mohd Faizal; Sabudin Sulastri; Zakaria Jamal Hazri (MATEC Web of Conferences, 2017)
Since the invention of fluidized bed systems to augment chemical reactions, numerous innovations were introduced to the system. These innovations result-in substantial improvement to the overall efficiency apart from resulting the fluidized bed system to become more compact. One of the innovations were the introducing of secondary air inside the bed so that a secondary motion in lateral direction can increase the amount of solid-gas interaction. This paper reviews various techniques proposed by researchers in providing secondary air inside the fluidized bed system. In general, four techniques were common in which the bed was named after: vortexing bed, cyclonic bed, rotating bed and swirling bed. Though resemble similarity, each of these beds were unique and comes with different advantageous. In conclusion, a fluidized bed system can be improved by the secondary motion in the bed which provides opportunities for further innovations.